Manajemen Bantuan Zakat Infak Sedekah (Zis) Dalam Perspektif Maqasid Al-Syari’ah di Baznas Kota Makassar - Nindhi Meyna Susilawati; Nurlaelah; Nur Setiawati (Program Pascasarjana Universitas Muslim Indonesia, 2023)
Managing zakat infaq and alms (ZIS) funds at the Amil Zakat Agency in Makassar City requires good management. Therefore, the Amil Zakat Agency is required to play an active role in achieving this. Makassar City's ZIS management, Maqasid Al-Syariah, was chosen as a benchmark used as an indicator of aid management with the aim of improving community welfare. The purpose of this study was to determine the effectiveness of Zakat, Infak, and Alms Assistance Management (ZIS) in the Maqsid Al-Syar'ah Perspective at BAZNAS Makassar City using a descriptive qualitative research approach. In the process of collecting data, the author uses several methods, namely the method of observation, interviews, and documentation. The results of this study indicate that the management of assistance in the management of Zakat Infak Alms funds for the Makassar City BAZNAS program has been in accordance with Maqsid al-Syar'ah; the thing that has had a major impact on the MAKASSAR SEJAHTERA program is the revolving fund assistance program for micro-enterprises, while the Ad-Din aspect of this is in accordance with the objectives of the Makasar TAKWA, HEALTHY MAKASSAR, and SMART MAKASSAR programs, although each has not been maximized; The effectiveness of ZIS BAZNAS Assistance Management in Makassar City still has various main problems, including: the coordination pattern of OPZ in general is not optimal; the understanding of zakat fiqh and regulations in regional BAZNAS leaders is generally still weak; the competence of regional BAZNAS leaders; the management and functions of regional BAZNAS; and the quality of HR BAZNAS AMI in general is still weak